Topic Discovery of Online Course Reviews Using LDA with Leveraging Reviews Helpfulness - Fetty Fitriyanti Lubis; Yusep Rosmansyah; Suhono H. Supangkat (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Despite the popularity of the Massive Open Online Courses, small-scale research has been done to understand the factors that influence the teaching-learning process through the massive online platform. Using topic modeling approach, our results show terms with prior knowledge to understand e.g.: Chuck as the instructor name. So, we proposed the topic modeling approach on helpful subjective reviews. The results show five influential factors: “learn easy excellent class program”, “python learn class easy lot”, “Program learn easy python time game”, and “learn class python time game”. Also, research results showed that the proposed method improved the perplexity score on the LDA model.